Dissection of Lower and Upper Jaws Could They Be Efficiently Examined Without Isolation From the Corpse - Afşin, Hüseyin; Uysal, Cafer; Boran, Tansev; Afşin, Feryal Kahraman (The Bulletin of Legal Medicine, 2001)
In some cases, for detailed intraoral examination it may be necessary that the upper and lower jaws of a corpse should be removed in such a way to cause the least traumatic change. It is difficult but compulsory to identify by dental examination the corpses particularly who/which are found to have foreign bodies such as stones and/or soil in the mouths because of being hurried under the ground and who have completed mortal rigidness or are frozen. At the end of this process, it is important that, the external view of the corpse not be spoiled. In this study a dissection technique which had been developed before was improved, and attempts were made to modifiy it. For this aim the muscular tissues sur-ronding the mouth of one case were dissected and the lower and upper jaws removed from the body by cutting the bone tissues. The most difficult problem faced when examining the structures forming the oral cavity is the elimination of mortal rigidness in cases in which it has reached a maximum level. Applying improper force on the teeth and mucosa may cause demage which makes it difficult to distinguish whether such damage has happened antemortem or postmortem. Even if it is possible for the mouth to be fully opened it is still not easy to obtain sample tissue and furthermore dental modelling or getting an x-ray of the area is impossible. External suturing following the autopsy in the case of an incorrect method applied while dissecting the cheeks may make the kins of dead person irritated. When identification is necessary, findings about the number of teeth, the number of decayed ones, fillings crowns and bridges should be recorded without fail. The modelling of the teeth is important from the view of making easy comparisons in future and obtaining reliable evidence. A good photography in which the teeth are clearly discernible will enable the dead persons relatives to remember his/her features that can not be described when asked to. A dental model may be used in proving whether marks of teeth on the accused belong to the victim. It may also be of some use in identifying the victim by DNA tests. The face is usually the target for blows. Traumatic findings on alveol of the theet such as .subluxation or partial fractures of the alveolar wall may go unnoticed in a classically carried out examination. Our study, clinical stages were photographed, and problem faced during the application of dissection were put forward and discussed. Key Words: Autopsy, tooth, forensic odontology